APPLICATION OF THE INTERNET OF THINGS FOR ENVIRONMENTAL MONITORING OF GRAPE LAND - Wahyu Kusuma Raharja (LPPM Poltek ST Paul, 2023)
The development of information and communication technology is growing rapidly. One of the focuses of development is Internet of Things (IoT) technology. Various applications can take advantage of this technology, including telemonitoring tools in agriculture, especially the land environment on grapevines in real time and remote control. Parameters that can be monitored include Soil Humidity, Light Intensity, Air Humidity and Air Temperature. This study aims to design and build a prototype of an IoT-based vineyard environmental telemonitoring tool. This research can be applied in smart farming, especially for grape farmers. The tool is made up of 3 sensors, namely DHT11 (Humidity, Temperature), LDR (Photoresistor/Light) and YL-69 (Moisture). Arduino ESP32 kit module as a processing unit for all light, temperature and humidity variables. The processing results are displayed on the Smartphone via the Blynk application. The output of this tool can also monitor grapevines through a camera and perform watering automatically using a water pump. Based on the instrument's accuracy test which was carried out on 3 parameters of the land environment and compared to similar tools, the results of the measurement of light intensity obtained an average accuracy of 72.85%. In the temperature test, the average accuracy result is 93.75%. In the soil moisture test, the average accuracy result is 87.25%.